Synthesis of a lithium–cyclopentadienide complex by addition of LiNTf2 to a zwitterionic fulvalene12. Issue 1 (29th November 2016) - Schmid, Dominic; Seyboldt, Alexander; Eichele, Klaus; Kunz, Doris
Abstract : LiNTf2 adds to a zwitterionic fulvalene yielding a η 5 -CpLi complex that is in equilibrium with its lithiocene at −80 °C as revealed by 7 Li NMR spectroscopy. Abstract : The synthesis of a η 5 -coordinated LiCp complex by simple addition of a Li-salt in benzene is presented. A strongly zwitterionic fulvalene serves as the Cp-precursor. Evidence for the coordination of Li + was obtained by the characterisitic 7 Li NMR chemical shifts, variable temperature experiments in solution and by X-ray structure analysis in the solid state.